DAMPAK PERKAWINAN DI USIA DINI (STUDI KASUS DI DESA KEDAWANG KECAMATAN NGULING KABUPATEN PASURUAN) - Yusrolana yusrolana; Fathurrahman Alfa; Dwi Ari Kurniawati (Jurnal Hikmatina, 2019)
Marriage is something sacred is worth worshiping to God, following the sunnah of the Prophet and carried out on the basis of sincerity and with a sense of responsibility. In Chapter 1 Article 1 of the Law of the Republic of Indonesia Number 1 of 1974 explains that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the One Godhead. The purpose of marriage as explained in the Qur'an is Ar-Rum verse 21 "And among the signs of His greatness is Allah created pairs for you of your own kind, so that you tend and feel secure to him, and Allah makes you among love and affection. Indeed, there are truly signs of God's greatness for those who think. The problems discussed in this article consist of two types, namely, how the factors of early marriage in Kedawang Village, and how the positive and negative effects of early marriage in Kedawang Village. In the step of getting the data in this study using by coming directly to the research site. For the method using qualitative descriptive methods. The results of this study were obtained by conducting observations, interviews, and documentation that showed that early marriage is still common, so that the marriage often has a negative impact, namely, in the form of divorce. The location of this study is located in Kedawang Village, Nguling District, Pasuruan Regency, East Java.Kata Kunci: Faktor, Dampak Positif Dan Negatif Perkawinan Usia Dini